Implementation of project management in state authorities - O. A. Zyablikova (Вестник университета, 2022)
The relevance of the study is due to the tasks that the President of the Russian Federation set for federal, regional and municipal authorities to grow the national and regional economy, increase its competitiveness and the effectiveness of public administration. Improving public administration and increasing its efficiency requires the development of a modern management methodology based on the introduction of a project approach. The purpose of the study is to develop practical recommendations aimed at improving the processes of project activities at the state level. The objectives of the study included reviewing the role of project activities, practices of implementing project management in the regions, identifying problems in the implementation of regional projects and programs and determining ways to solve them. The article uses graphical and tabular methods of data visualization, statistical and general scientific research methods. As a result of the study, the practice of implementing project management was analyzed in detail on the example of four regions of the Russian Federation, which were among the first to introduce the project approach and showed high practical results of project management. A special place in the study is occupied by the algorithm developed for executive authorities for the transition to a project-oriented management system, which increases the flexibility of the management structure, allows you to create an infrastructure for project activities, determine the design competencies of specialists and increase project maturity.